MENGUKUR EFEKTIVITAS PELATIHAN JARAK JAUH PEGELOLAAN DAN PERTANGGUNGJAWABAN KEUANGAN DESA ANGKATAN I TAHUN 2022 DI BALAI DIKLAT KEUANGAN MALANG - Nawawi, M. Bahrun (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2024)
Improving the competence of village officials in managing and being accountable for village finances can be done through education and training. This research was conducted to find out the effectiveness of organizing long-distance training on village financial management and accountability for batch I in 2022 at the Malang Financial Education and Training Center (BDK). This research is a one-group pretest-posttest research design and the analysis uses the Wilcoxon Matched-pairs test. The population of this study were all participants of the first long-distance village financial management and accountability training in class 2022 at BDK Malang. The results showed that the average post-test score was greater than the average pre-test score. Based on these results, it can be concluded that the long-distance training on village financial management and accountability for batch 1 in 2022 at BDK Malang has proven to be effective in increasing the competency of the training participants. By increasing the competency of village officials in managing village finances, their performance and accountability will become better.